Gent, van den oudsten tijd tot heden: geschiedkundige beschrijving der stad - Potter, Frans de 1834-1904 (Ghent Annoot-Braeckman, 1883)
Published in eight volumes between 1883 and 1901, De Potter's monumental study is far from perfect, but the work remains the most important frame of reference for the study of Ghent history. What is unique is that De Potter does not provide a chronological overview, but that he takes the reader through the streets of the city like an experienced guide and stops at almost every building to explain it. In addition, De Potter had numerous unpublished archive documents appear in print for the first time.
Frans de Potter was the co-founder of the Flemish Davidsfonds
Keywords: Past; 19th Century (1801-1900); History; Ghent (Belgium)